2008
DOI: 10.1021/ci8001167
|View full text |Cite
|
Sign up to set email alerts
|

MedusaScore: An Accurate Force Field-Based Scoring Function for Virtual Drug Screening

Abstract: Virtual screening is becoming an important tool for drug discovery. However, the application of virtual screening has been limited by the lack of accurate scoring functions. Here, we present a novel scoring function, MedusaScore, for evaluating protein-ligand binding. MedusaScore is based on models of physical interactions that include van der Waals, solvation and hydrogen bonding energies. To ensure the best transferability of the scoring function, we do not use any protein-ligand experimental data for parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
225
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 177 publications
(227 citation statements)
references
References 49 publications
2
225
0
Order By: Relevance
“…Empirical Knowledge-Based DOCK [32] AutoDock [34] SMoG [82] AutoDock [34] GlideScore [37] DrugScore [62] GoldScore [35] ChemScore [60] PMF_Score [83] ICM [46] X_Score [66] MotifScore [84] LigandFit [47] F_Score [73] RF_Score [85] Molegro Virtual Docker [48] Fresno [75] PESD_SVM [86] SYBYL_G-Score [73] SCORE [76] PoseScore [87] SYBYL_D-Score [73] LUDI [77] MedusaScore [74] SFCscore [78] HYDE [79] LigScore [80] PLP [81] …”
Section: Force-field-basedmentioning
confidence: 99%
“…Empirical Knowledge-Based DOCK [32] AutoDock [34] SMoG [82] AutoDock [34] GlideScore [37] DrugScore [62] GoldScore [35] ChemScore [60] PMF_Score [83] ICM [46] X_Score [66] MotifScore [84] LigandFit [47] F_Score [73] RF_Score [85] Molegro Virtual Docker [48] Fresno [75] PESD_SVM [86] SYBYL_G-Score [73] SCORE [76] PoseScore [87] SYBYL_D-Score [73] LUDI [77] MedusaScore [74] SFCscore [78] HYDE [79] LigScore [80] PLP [81] …”
Section: Force-field-basedmentioning
confidence: 99%
“…The terms on the right side of Equation 2 were determined with Medusa using structural models of the closed and open states of WT and mutant RyR1. In the case of homology models, such calculations are good predictors of the net effect of mutation (stabilization or destabilization), but the magnitude of ⌬⌬G is not highly accurate (40). Thus, in this study, we used the ⌬⌬G values to predict if there will be an increase or decrease in P o of mutant channels, but not the extent of change in P o .…”
Section: Wtmentioning
confidence: 99%
“…Gohlke et al 61 and Velec et al 80 have also reported that DrugScore shows better ranking than the scoring functions within the docking programs. Furthermore, a recent study Dokholyan and colleagues 81 showed that the success rate of their docking results was improved to 85% by consensus scoring with DrugScore for a docking decoy set consisting of 100 complexes. Likewise, our binding affinities got improved by rescoring the lowest energy pose by DrugScore.…”
Section: Assessing the Scoring Accuracy With Drugscorementioning
confidence: 99%